Ficções de uma poética autobiográfica - Oliveira, Paulo Wagner Moura de (2012)
In this dissertation, we realize a critical analyse of Wanderley Wasconcelos’ poetry, a matogrossense writer, aiming to comprehend the time and memory configuration, at the perspective of the bergsonian concept about ‘duration’, as the criative nucleus able to join in the same signic plan: the ‘real’, ‘fictitious’ and ‘imaginary’. In the poems there are lyrical Self, a literary alterego of the athor, responsible persona by the liberation of the confessional Self. A ‘lyrical Self’, that reliving the idyllical past childhood, in contradiction at the aldult present, with his difficulties to the social transformations, witnessing from the historical- geographic referencial, in Araguaian-MT occupancy context. In this meeting of times, one of mythical and idealized, identified with childhood period, and the other, with historical, social and outside, provoking in the ‘lirycal Self’, feeling of an uprooting and an alienation inf front of the reality. In spite of the conflict, the evocation of memories finish to join at actually existence.